Pushing bonds over the edge: Monetary policy and municipal bond liquidity - John Bagley; Stefan Gissler; Kent Hiteshew; Ivan T. Ivanov (Federal Reserve Bank of Chicago, 2023)
We examine the role of institutional investors in monetary policy transmission to asset markets by exploiting a discontinuous threshold in the tax treatment of municipal bonds. As bonds approach the threshold, mutual funds, the primary institutional traders in the market, dispose of the bonds at significant risk of falling below the threshold. This is driven by mutual funds anticipating future illiquidity. Once bonds cross the threshold, their liquidity declines and illiquidity-induced yield spreads increase substantially as retail investors become more important in price formation. Unexpected monetary policy tightening sharply reduces trading activity, amplifying the path to illiquidity in the market.
Keywords: 330; Monetary Policy; Municipal Bonds; Institutional Investors; Asset Liquidity